SSFIT IN THE SPORTS TRAINING OF ELITE FEMALE BOXERS A - BADALOVA , Shaxnoza («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
s article presents an assessment of the effectiveness of CrossFit exercises in improving the athletic performance of elite female boxers. The study analyzed the impact of the CrossFit system—one of the modern sports technologies—on the development of physical qualities such as strength, endurance, agil- ity, and coordination. The results of the experiment showed that CrossFit exercises provide a compre- hensive physical load and significantly improve the overall performance of female athletes.